Occupational exposure assessment to volatile organic compounds (VOC). A case study in a chemical company - Villalobos-Morales, Josué A. (2024)
The present investigation project was developed in a chemical company which develops, manufactures and trade resins for paints and cosmetic products.  The occupational exposure of workers assessment (OEWA) to volatile organic compounds (VOC) was determined by using a methodology named "Chemical risk: systematic for hygienic evaluation", develop by the French National Institute for Security Research (INRS). The assessment analysed general aspects such VOC environmental concentrations and the evaluation of occupational risk factors chemical products handling and their storage conditions. To gather the necessary data, in situ instrumental tools as site inspections, checklists, and surveys, among others were used. The global evaluation chemical risk assessment also included the following: production process analysis, infrastructure conditions inspection and quantification of internal atmospheric pollutants through the gas chromatography technique (GC). Related with the experimental VOC determination, a total of 22 chemical pollutants were quantified (GC Technique). The N-Butyl was the only compound that exceeded the Threshold Limit Value (TLA) recommended by the Spain National Institute for Safety and Health (INSSBT). The N-butyl is related to health effects such skin allergies and asthma. The results gathered from the OEWA to VOC shows high chemical risk level for 4 chemical compounds. These results indicate the need to prevent worker health effects by modification of some labour conditions. As part of the research and to correct and to prevent future chemical risks an action plan was develop, especially focused on the handling, exposure, and use of chemical volatile organic compounds.